SEASONAL VARIATIONS IN THE TOTAL CHOLESTROL CONTENT OF THE LIVER OF CAT FISH. HETEROPHUESTES FOSSILIS (BLOCH). - SHRENI, KALPANA D; JAFRI, A K (Fishery Technology, 2017)
Variations in the total liver cholesterol content of Heteropnuestes fossilis followed weH defined seasonal cycle. A decline was recorded during the period when the gonads were passing through the peak ripe stage. The highest value of the cholesterol was however attained before this phase of gonad maturation Concentration pattern of liver cholesterol seemed related to variations in the cholesterol metabolism of the fish, necessitated, besides other factors, by the demand for sex hormones. A possibility of the influence of feeding intensity on liver cholesterol content has also been indicated.